2007
DOI: 10.1024/0300-9831.77.1.22
|View full text |Cite
|
Sign up to set email alerts
|

B-Vitamins and Homocysteine in Spanish Institutionalized Elderly

Abstract: There is a high prevalence of vitamin B deficiency and hyperhomocysteinemia in the studied population. Our data confirm the influence of these vitamins, especially folate, on tHcy levels, but hyperhomocysteinemia cannot be used as the only diagnostic criterion to detect subclinical vitamin deficiency in elderly people, especially to detect vitamin B12 deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 76 publications
3
32
2
1
Order By: Relevance
“…Finally, in agreement with Gonzalez-Gross's observation (24), and on the basis of our own experience, given the high prevalence of hyperhomocysteinemia (frequently due to vitamin B deficiency) careful monitoring of the metabolic markers of cobalamin status is suggested (26,27).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Finally, in agreement with Gonzalez-Gross's observation (24), and on the basis of our own experience, given the high prevalence of hyperhomocysteinemia (frequently due to vitamin B deficiency) careful monitoring of the metabolic markers of cobalamin status is suggested (26,27).…”
Section: Discussionsupporting
confidence: 57%
“…There is concern about subtle cobalamin deficiency, especially in populations at risk. As reported by Miller et al (23) in a study of an elderly cohort, and confirmed by Gonzalez-Gross et al (24), measurement of both HoloTC and tB 12 concentrations provide better screening for cobalamin deficiency than either assay alone.…”
Section: Discussionmentioning
confidence: 50%
“…This may be due to the preparation of samples for RBC folate measurement which requires more laborious steps than for sFolate. Additionally, both folate markers should be measured to assess if there is a mixed deficiency between folate and vitamin B 12 [1]. However, MMA measurement is important to distinguish between vitamin B 12 and folate deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin B 12 levels decreases with age [1], which means that deficiency risk increases in parallel with age [2][3][4]. Therefore, subclinical deficiency is quite more prevalent in the elderly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation